Conselho editorial (Secretariado Executivo em Revist@, 2017)
Secretariado Executivo em Revist@Nº 12/2016ISSN 1809-2802Acesso: www.upf.br/seerConselho editorial desta edição:Profa. Ma. Aline CantarottiProfa. Dra. Cibele Barsalini MartinsProfa. Ma. Cibelle da Silva SantiagoProfa. Ma. Chussy Karlla Souza AntunesProfa. Ma. Daniela Giareta DuranteProfa. Ma. Eliane WamserProfa. Dra. Emili Barcellos Martins SantosProfa. Ma. Fernanda Cristina SanchesProfa. Ma. Josete Alzira Passamani StoccoProfa. Ma. Keila Raquel WenningkampProfa. Ma. Maria do Carmo Assis TodorovProfa. Ma. Maria Elisabete Mariano dos SantosProfa. Ma. Maria Luzitana Conceição dos SantosProf. Me. Rodrigo MüllerProfa. Dra. Rosimeri Ferraz SabinoOrganização:Profa. Ma. Caroline de Fátima Matiello Vaz